Cavity-promotion by pillar[5]arenes expedites organic photoredox-catalysed reductive dehalogenations. Issue 75 (31st August 2021) - Schmidt, Maximilian; Esser, Birgit
Abstract : Preassociation of the substrate close to the photoredox catalyst increases its efficiency, shown using pillarene-bound phenothiazines in the reduction of alkyl bromides. Abstract : The efficiency of the photo-induced electron transfer in photoredox catalysis is limited by the diffusional collision of the excited catalyst and the substrate. We herein present cavity-bound photoredox catalysts, which preassociate the substrates, leading to significantly shortened reaction times. A pillar[5]arene serves as the cavity and phenothiazine as a catalyst in the reductive dehalogenation of aliphatic bromides as a proof of concept reaction.